Cross-Talk Between Mitochondrial Fusion and the Hippo Pathway in Controlling Cell Proliferation During Drosophila Development. Issue 4 (1st August 2016) - Deng, Qiannan; Guo, Ting; Zhou, Xiu; Xi, Yongmei; Yang, Xiaohang; Ge, Wanzhong
Abstract: Cell proliferation and tissue growth depend on the coordinated regulation of multiple signaling molecules and pathways during animal development. Previous studies have linked mitochondrial function and the Hippo signaling pathway in growth control. However, the underlying molecular mechanisms are not fully understood. Here we identify a Drosophila mitochondrial inner membrane protein ChChd3 as a novel regulator for tissue growth. Loss of ChChd3 leads to tissue undergrowth and cell proliferation defects. ChChd3 is required for mitochondrial fusion and removal of ChChd3 increases mitochondrial fragmentation. ChChd3 is another mitochondrial target of the Hippo pathway, although it is only partially required for Hippo pathway-mediated overgrowth. Interestingly, lack of ChChd3 leads to inactivation of Hippo activity under normal development, which is also dependent on the transcriptional coactivator Yorkie (Yki). Furthermore, loss of ChChd3 induces oxidative stress and activates the JNK pathway. In addition, depletion of other mitochondrial fusion components, Opa1 or Marf, inactivates the Hippo pathway as well. Taken together, we propose that there is a cross-talk between mitochondrial fusion and the Hippo pathway, which is essential in controlling cell proliferation and tissue homeostasis in Drosophila .